Analisis Tingkat Digital Maturity Model Pada UMKM - Cahyadi, Luh Diah Citra Resmi; Artaningrum, Rai Gina (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
The digitalization process carried out by MSMEs still experiences several obstacles, including a lack of understanding and ability to digitize, resources and capital, so it is important to evaluate the quality of MSMEs' digitalization. Without evaluation, it will be difficult to measure the degree of digitalization. However, previous research has still minimally evaluated the maturity of digilization in Indonesia. In terms of digitalization, Bank Indonesia stated that Bali has a Fairly Good digitalization category. However, no evaluation research has been found on digitalization maturity in MSMEs in Bali. This research is a solution for measuring and evaluating DMM for MSMEs in Bali, especially Denpasar City, which produces models, methods and studies for measuring and evaluating DMM in other areas. This research used a simple random sampling technique which obtained 113 MSME respondents in Denpasar City. The data was processed using the K-Means Clustering Model. The results of this research showed that 80 MSMEs were in the emerging phase, 1 MSME was in the progressing phase, 1 MSME was in the established phase and 31 MSMEs were in the leading phase.